Village Funds After the Emergence of the Village Law (Study of the Use of Village Funds in Providing Cash Direct Funds ‘BLT’ in Kelet Village during the Pandemic) - Rokhman Adi Putera Nugraha; Nuria Siswi Enggarani (Law and Justice, 2021)
Objective: Knowing the basis for implementing the use of village funds in providing Cash Direct Funds (BLT) in Kelet Village and examining the effectiveness and barriers to using village funds in providing Cash Direct Funds in Kelet Village as well as the criteria for Cash Direct Funds recipients in Kelet Village.Method: The research method used is a normative model with a statutory approach with descriptive analysis in nature. Types and sources of data were obtained from the results of an inventory of literature studies on official documents of laws and regulations related to Cash Direct Funds. The data collection method uses the literature study technique, which is carried out by searching, recording, taking inventory, and analyzing the material content data from the body and previews contained in the statutory regulations related to Cash Direct Funds. The data analysis model uses a deductive thinking pattern in order to draw a conclusion.Finding: In Kelet Village, a cash direct funds program has been implemented which has been legalized through Village Head Regulation No. 6/2020 About Village Cash Direct Funds to Beneficiary Families Due to the COVID-19 Pandemic. The Village Head Regulation applies because there is a regulatory order from Law No. 2/2020 concerning Stipulation of Government Regulation In Lieu of Law No. 1/2020 concerning State Financial Policy and State Financial System Stability for Handling the COVID-19 Pandemic and its derivatives which include: Minister of Finance Regulations, Village Government Regulations, and Ministry of Home Affairs Instructions for the implementation of Cash Direct Fund.Novelty: This research was conducted because of a policy that was passed by the government during the COVID-19 pandemic, which caused a lot of misunderstanding for the public in responding to applicable policies.